2022
DOI: 10.3390/antiox11050933
|View full text |Cite
|
Sign up to set email alerts
|

OGG1 in Lung—More than Base Excision Repair

Abstract: As the organ executing gas exchange and directly facing the external environment, the lungs are challenged continuously by various stimuli, causing the disequilibration of redox homeostasis and leading to pulmonary diseases. The breakdown of oxidants/antioxidants system happens when the overproduction of free radicals results in an excess over the limitation of cleaning capability, which could lead to the oxidative modification of macromolecules including nucleic acids. The most common type of oxidative base, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 123 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…OGG1 has also been widely studied in the context of tumors and lung injuries. Recent studies have found that the regulation of gene transcription of OGG1 seems to be as important as the effect of base excision and repair [135]. How OGG1 regulates downstream gene in patients with CKD is worthy further exploration (Figure 5).…”
Section: Ogg1 In Ckdmentioning
confidence: 99%
“…OGG1 has also been widely studied in the context of tumors and lung injuries. Recent studies have found that the regulation of gene transcription of OGG1 seems to be as important as the effect of base excision and repair [135]. How OGG1 regulates downstream gene in patients with CKD is worthy further exploration (Figure 5).…”
Section: Ogg1 In Ckdmentioning
confidence: 99%